Study of NiO Nanoparticles Synthesis by Sol Gel Method, Its Characterization and Biological Application (International Journal of Scientific Research in Science and Technology, 2024)
The present research work focuses on synthesis of Nickel oxide nanoparticles by sol-gel method, their characterization and the antibacterial effect of NiO on E. coli (NCIM 2065) and Bacillus subtilis (NCIM2063).Sol-gel technique is one of the simple, cost effective, environmentally safe technique for synthesis of Nickel oxide nanoparticles by optimizing reaction parameters to provide the good biological properties and applications. The green color Nickel oxide nanoparticles was synthesized, washed with distilled water, dried and calcinated at 5000c for 5 hours was investigated byFourier transform infrared spectroscopy, The X-ray powder diffraction, Scanning Electron Microscopy, Energy dispersive X-Ray spectroscopyandto usedstudy the antibacterial effect of NiO on E. coli (NCIM 2065)andBacillus subtilis (NCIM2063).